Pendampingan Pastoral bagi Pekerja Migran Korban Penipuan Lowongan Kerja di Media Sosial - Sianturi, Lusiana; Silitonga, Imel Grace; Panjaitan, Mawar E (Sekolah Tinggi Diakones HKBP, 2025)
Migration is a global phenomenon that continues to grow alongside advances in digital technology, but this development has also given rise to rampant job vacancy scams on social media that ensnare prospective migrant workers. Many victims suffer material losses, loss of documents, violence, and even exploitation as a result of illegal recruitment. This study uses a literature review method to analyze the forms of digital fraud and examine the role of the church in providing pastoral care for victims. The results of the study show that the church has a moral and spiritual responsibility to provide holistic services through the four pastoral functions according to Clebsch and Jaekle: healing, strengthening, guiding, and reconciling. This assistance is not only spiritual in nature, but also manifested in concrete actions such as legal aid, counseling, protection, digital literacy education, and the use of technology for online services. This study emphasizes that the church needs to be an agent of love and restoration amid the challenges of the digital age, while also maintaining the dignity of migrant workers as the image and likeness of God.